Reservas de caixa e ameaças biológicas: um estudo das políticas de cash holding frente ao choque exógeno causado pela pandemia da COVID-19 - Gomes, Poliana Carine Silva (2021)
The objective of this research is to analyze whether Brazilian publicly traded companies manage their cash reserves when exposed to an exogenous shock, through an almost natural experiment, caused by the pandemic of COVID-19. The study sample included 273 Brazilian companies, listed on B³ and used the OLS Regression method with an estimate of difference-in-differences. The survey results are that the COVID-19 pandemic positively impacted the cash reserves of the companies analyzed, both using the year 2019 and the year 2018 as an exogenous pre-shock period. It was also identified that macroeconomic variables such as GDP, interest rates and inflation have an influence on cash retention in times of health crises. It is understood that this growth in cash reserves after exogenous shock is mainly due to the presence of uncertainties in the generation of future cash flows, encouraging an increase in the levels of cash reserves to manage fixed costs and business maintenance and avoiding the need to use third party capital, given the preference for liquidity. It was also identified that financially restricted companies retained cash to a lesser ext ent than unrestricted companies.